PERAN PSIKOLOGI PENDIDIKAN UNTUK PENCEGAHAN BULLYING DI SEKOLAH DASAR - Suhadah Suhadah; Avi Valentri (STAI Darul Qalam Tangerang, 2025)
This study aims to analyze and synthesize the crucial role of educational psychology in formulating comprehensive strategies for preventing and handling bullying in elementary schools. Bullying is a serious problem that causes broad psychological impacts, including decreased mental health, increased anxiety, and loss of motivation and academic achievement in victims. This literature review identified that the roots of bullying behavior often lie in psychological factors such as poor emotional regulation in perpetrators, the need for dominance, and the influence of group conformity. The method used was a qualitative literature study, with a critical analysis of various scientific sources to classify the causes, impacts, and relevant intervention models. The results of the synthesis indicate that effective prevention must be based on educational psychology. Key strategies include the systematic implementation of Social-Emotional Competence (SEL) programs to instill empathy and relationship skills in all students. In addition, cognitive-behavioral interventions are needed to change the aggressive mindset of perpetrators, as well as strengthening self-esteem and assertiveness skills in victims. This study also emphasizes the importance of activating the role of witnesses (bystander intervention) and the use of the Restorative Justice model to restore relationships. Thus, educational psychology serves as a scientific framework for creating a safe, supportive, and child-friendly school climate.